A novel de novo NLRC4 mutation reinforces the likely pathogenicity of specific LRR domain mutation - Chear, Chai Teng (Clinical immunology (Orlando, Fla.), 2020)
Copyright © 2020 The Authors. Published by Elsevier Inc. All rights reserved.